All-Consuming Passions: Fire Metaphors in Fiction - Jonathan CHARTERIS-BLACK (E-REA)
This paper discusses the role of metaphor in describing intense romantic feelings relating to love, lust and desire in American fiction. I propose that ‘passion’ integrates notions of romantic ‘love’ with the related concepts of ‘lust’ and ‘desire’. Using the fiction section of the Corpus of Contemporary American English I offer empirical evidence that fictional accounts of intense romantic feelings are characterised by two related types of metaphor: those based on the experience of heat and fire, and those based on the experience of physical or natural forces. These can be represented as LOVE/ LUST/ DESIRE IS FIRE and EMOTIONS ARE NATURAL FORCES. These metaphors are employed to understand various aspects of romantic feelings including their cause, their effect and the level of intensity with which they are experienced by fictional characters. I explain how fire and heat are related through metonymy and how these are both related to fire through the force dynamic model (originally proposed by Talmy 1988 and developed in Kövecses 2000) to account for fictional representations of the passions, especially as regards variations in their intensity. I also discuss the question of how far empathy and sensual arousal on the part of a reader of romantic fiction may be triggered in the brain by descriptive accounts of people engaging in romantic, affective and, or, sexual activities. Finally I offer two new metaphors specifically for seduction: SEDUCTION IS PLAYING A GAME and SEDUCTION IS FISHING and I suggest possible psychological reasons for their appeal to authors and readers of fiction.